2003
DOI: 10.7748/ns.17.26.40.s53
|View full text |Cite
|
Sign up to set email alerts
|

Prison in-reach mental health nursing

Abstract: Surveys have shown that over 90 per cent of the prison population have a diagnosable mental illness, substance abuse problem, or both (ONS 1998). There is general agreement that although there are areas where practice is excellent, practice is not consistent across England and Wales, and often does not equate to standards in the NHS. In 2001 the Department of Health and the prison service set out their joint approach to the modernization of mental health services in prisons (DoH 2001), and proposed mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Inreach services were envisaged as being equivalent to Community Mental Health Teams, which provide specialist mental health input to the community. Evaluation of inreach has, to date, been limited to studies into operational, rather than clinical, considerations (Armitage et al 2003; Meiklejohn et al 2004; Steel et al 2007; Brooker & Gojkovic, 2009). Such studies have shown wide variation in models of care, poor awareness among prison discipline staff about the role of inreach leading to inappropriate referrals, and problems implementing the Care Programme Approach (CPA; DH, 1990) in custody (Telfer, 2000; Lee, 2003; Meiklejohn et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Inreach services were envisaged as being equivalent to Community Mental Health Teams, which provide specialist mental health input to the community. Evaluation of inreach has, to date, been limited to studies into operational, rather than clinical, considerations (Armitage et al 2003; Meiklejohn et al 2004; Steel et al 2007; Brooker & Gojkovic, 2009). Such studies have shown wide variation in models of care, poor awareness among prison discipline staff about the role of inreach leading to inappropriate referrals, and problems implementing the Care Programme Approach (CPA; DH, 1990) in custody (Telfer, 2000; Lee, 2003; Meiklejohn et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A further role for teams related to education and training for discipline staff. In common with previous reports teams were largely nursing led (Armitage et al, 2003), relying on the prison primary health-care services for medical input.…”
Section: Resultsmentioning
confidence: 53%
“…The team, made up of mental health professionals, may receive referrals from a range of sources. They then provide a multidisciplinary mental health assessment of need and risk, providing the prison health care team with advice and support to develop a care plan, and providing prisoners with appropriate medical and psychosocial interventions (Armitage, Fitzgerald, & Cheong, 2003). Prison in-reach services therefore seek to provide an equivalent service to that provided by community mental health teams in UK community settings, as determined by national standards (DoH, 1999;Wilson, 2004).…”
Section: Policy Contextmentioning
confidence: 99%
“…However, since the publication of the Reed Report (Department of Health and Home Office, 1992), the development of closer links between probation and other elements of the criminal justice system with health and social care agencies has been encouraged through government policy initiatives (see, for example, NHS Executive and HM Prison Service, 1999). These include the establishment of court diversion schemes, prison in-reach services (Armitage et al, 2003), police station diversion initiatives (James, 2000) and projects in approved premises such as those highlighted above (Geelan et al, 2000;Nadkarni et al, 2000).…”
Section: Introductionmentioning
confidence: 99%